MEMAKNAI DANA PENGENTASAN KEMISKINAN DALAM PENGANGGARAN DAERAH - Barbara Yessi Taruk Allo; Fransiskus Randa; Yakobus K Bangun (AJAR, 2019)
This study aims to understand the face of poverty and the use of poverty alleviation funds in regional budgeting. The study was conducted in Makassar City, South Sulawesi by using case study approach. Data collection was done by interview and observation. In-depth interviews were conducted for povertystricken actors and budget managers of poverty funds. This research uses qualitative approach with case study analysis method which according to Creswel can be done through categorization stage, interpretation of pattern formation and naturalistic generaliation. The results show that there are three categories of poor people in the city of Maksassar namely vagrants and beggars, unemployed and poor fishermen. In the potency of policy and government budgeting behavior has been to eradicate the program of alleviation through increasing poverty alleviation budget allocation, but the fulfillment is not necessarily to alleviate poverty in Makassar City. This is because poverty is often used as a tool of exploitation by society and also as a political tool by the government.